LifeFinder an instructional look at the work of photographer Jeremy Cowart - Cowart, Jeremy; Arias, Zack.; Jeremy Cowart Photography, Inc. (Franklin, Tenn. : Jeremy Cowart Photography, Inc., 2010)
Professional photographer Jeremy Cowart shares his thoughts on photograpy and offers an inside view of his workflow, technique, and creative process. The program also includes eight behind-the-scenes looks at photoshoots, narrated by Cowart.
Disc 1. Interview by Zack Arias (28 min.) -- Vision toolkit (32 min.) -- Raw workflow (15 min.) -- 10 questions (13 min.) -- Locations and libraries (13 min.) -- Projects of purpose (26 min.) -- Tour photography (31 min.) -- Disc 2. Band (The Civil Wars, 17 min.) -- Male musician (Matt Wertz, 6 min.) -- Female musician (Caitlin Crosby, 20 min.) -- Experimentation (Imogen Heap, 20 min.) -- Actress/publicity (Tiffany Dupont, 7 min.) -- Performer/publicity (Chase Benz, 16 min.) -- Fashion (On location, 22 min.) -- Fashion (Seamless, 8 min.).
DVD, NTSC.
Keywords: Cowart, Jeremy; Photography -- Technique; Photography -- Digital techniques; Nonfiction films; Instructional films